Pengaruh Layanan Bimbingan Kelompok terhadap Pencapaian Tugas Perkembangan Remaja Awal dalam Aspek Kemandirian Emosional (Studi Eksperimen di SMP Frater Padang) - Sihotang, Nurjelita; Yusuf, A Muri; Daharnis, Daharnis (Konselor, 2013)
Teenagers have developmental task, one of them is emotional independence aspect. If the task could not be completed, it will cause the unhappiness for individual as well as the difficulties in solving the next developmental tasks. Teens that do not have emotional independence will always be dependent on parents or other adults so that when the teenagers growing up would have difficulty in completing development tasks. This research is a pre-experiment design of The One Group Pretest-Posttest Design. Subjects in this study were 10 students eighth grade of SMP Frater Padang. To determine the amount of sample used purposive random sampling technique. Data analysis technique uses the Wilcoxson Signed Rank Test. The findings of this study are there are significant differences between pretest and posttest conditions achievement early adolescent developmental tasks in the emotional aspects of students' independence. Based on the findings above, it can be concluded that the achievement of the group guidance can affect the early adolescent developmental tasks on the emotional aspects of self-reliance